1994
DOI: 10.1111/j.1365-2796.1994.tb01106.x
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and gastrointestinal dysfunction as prognostic factors for survival in familial amyloidotic polyneuropathy

Abstract: The investigation disclosed that a short time interval between the onset of neurological and of gastrointestinal symptoms is associated with a decreased survival time. The mBMI was closely related to time before death, duration of gastrointestinal disturbances, malabsorption and functional capacity. The mBMI appears to be well suited to monitoring disease progress and gives prognostic information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
154
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(158 citation statements)
references
References 20 publications
4
154
0
Order By: Relevance
“…The mBMI of patients who died after transplantation tended to be lower than those in patients with good outcomes, except in one patient who died of endometrial carcinoma 4 years 11 months after transplantation. Our results regarding mBMI support those of previous reports (20,21), indicating that the nutritional state of FAP patients before transplantation is an important factor in predicting their post-operative state.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The mBMI of patients who died after transplantation tended to be lower than those in patients with good outcomes, except in one patient who died of endometrial carcinoma 4 years 11 months after transplantation. Our results regarding mBMI support those of previous reports (20,21), indicating that the nutritional state of FAP patients before transplantation is an important factor in predicting their post-operative state.…”
Section: Discussionsupporting
confidence: 91%
“…This index was reported to be correlated well with the prognosis of FAP patients after transplantation in foreign countries (20,21). The mBMI of patients who returned to their normal lives after liver transplantation in our country were significantly higher than those in hospital or recuperating at home at follow-up after more than one year.…”
Section: Discussionsupporting
confidence: 66%
“…45 In Sweden, survival does not appear to be correlated with age of onset. 26 The expression of the trait varies between different families and areas. 42 A study of the prevalence of the ATTR Val30Met mutation in northern Sweden showed that 1.5% of a population of 500,000, i.e., 7,500 individuals, carried the trait, although only approximately 200 cases are known, giving the trait a penetrance of less than 5%.…”
Section: Prognostic Factors For Survival After Liver Transplantation mentioning
confidence: 99%
“…51 We developed a modified body mass index (mBMI) in which BMI is multiplied by serum albumin (in grams per liter) to compensate for edema. 26 This index has proved valuable in patient selection, and we are now reluctant to list a patient for transplantation who has an mBMI less than 700 and will not perform transplantation on a patient with an mBMI less than 600. 37,60,89 The difference in mBMI from selection to transplantation is caused by the interval of approximately 6 months from referral to transplantation for Swedish patients.…”
Section: Gastrointestinal Impairmentmentioning
confidence: 99%
See 1 more Smart Citation